Digital Transformation In Maritime Education System Quality, Digital Competence, And Administrative Performance - Durratun Nashihah, Citra Afaf (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This qualitative study investigates the digital transformation of administrative services at the Sekolah Tinggi Ilmu Pelayaran (STIP), Indonesia's prominent maritime education institution. It examines the interplay between the quality of the SRIKANDI application system, the digital competence of civil servants (ASN), innovations in digital archive governance, and their collective impact on administrative performance. Data collected through in-depth interviews and focus group discussions with administrative staff revealed that high system quality, particularly its relevance to maritime-specific tasks, combined with strong digital competence, served as foundational enablers. These factors catalyzed significant innovation in digital archive management, which acted as the critical mechanism for improving performance. The transformation resulted in substantially enhanced efficiency, accuracy, and service delivery, directly supporting STIP's core mission. The findings underscore that successful digitalization in specialized educational contexts is a socio-technical endeavor, reliant on the synergy between tailored technology and a empowered workforce, rather than on technological implementation alone. This research provides a validated model for maritime education institutions navigating similar digital transitions.